Genetic and environmental factors affecting body weight of Nellore cattle raised on pastures in São Paulo state, Brazil - Silva, Luiz Otávio C. da; Rosa, Antonio do N.; Nobre, Paulo Roberto C.; Milagres, João C.; Evangelista, Silvio Roberto M. (Pesquisa Agropecuaria Brasileira, 2014)
Birth weight (BW) and body weights at 205 (WW), 365 (YW) and 550 days (EW) of Nellore cattle raised on pastures were analysed. The animals were born from 30 herds of north São Paulo State, from 1976 throught 1981. The least squares means (kg) for BW, WW, YW and EW were respectively 28.6, 148.8, 206.8 and 265.2. Males BW, WW, YW and EW were superior to the same female measurements (P<.01). Only BW was not affected by year of birth. Otherwise WW, YW and EW decreased (P<.01) along time. Calves born during first season (Oct-December) had the greatest BW (P<.05). Those from fourth season (Jul-September) were the heaviest at weaning. For YW the maximum was obtained by animals from third season (Apr-June). Calves born from July throught December had greater EW (P<.05) than those from second season and third. The year x season interaction was significant for BW (P<.05) and for WW, YW and EW (P<.01). Herd and sire/herd affected all body weights and the age of dam had a quadratic influence (P<.01) on BW and WW. The heritability estimates for BW.WW. YW and EW, were respectively, 34±.04;.26±04;,29±06;and.25±.08. Four selection criteria were discussed, based on the direct and correlated genetic response and selection of animals at 365 days was suggested.